A Comparative Examination of Compensation Frameworks for Unjust Terminations: Insights from Diverse Jurisdictions - Edward Meli; Bjorn Camilleri; Luana Agius (European Scientific Journal, ESJ, 2024)
This study provides a comprehensive analysis of the compensatory systems for unfair dismissals in Europe, particularly in England, Malta, France, Portugal and Italy, examining their legal foundations, procedural mechanisms, and remedial approaches. Drawing on statutory provisions, landmark cases and scholarly commentaries, this analysis reveals both convergences and divergences in the five jurisdictions’ approaches to protecting employee rights and promoting social justice. While England’s framework emphasises procedural regularity and reasonableness, Malta’s regime adopts a broader concept of fairness, whereas France places significant value on the concept of transparency, Portugal’s system promotes stability and Italy’s system prioritises job security and reinstatement. This study underscores the importance of comparative analysis in fostering dialogue, collaboration, and knowledge-sharing amongst stakeholders to develop more robust, responsive, and inclusive legal frameworks that safeguard workers’ rights and ultimately promote social cohesion.